4P Increase Customer Loyalty - Ifan Sadewa (Siber Nusantara Research, 2024)
The This study examines how the elements of the marketing mix, known as the 4Ps (Product, Place, Promotion, and Price), affect customer loyalty. Based on a literature review covering books, internet sources, and international and national journals, it was found that each element of the 4Ps has a significant influence on customer loyalty. Quality and innovative products tend to strengthen customer trust and satisfaction, which in turn increases loyalty. Strategic placement facilitates customer access to the product, thereby increasing the chances of repeat purchases. Effective promotions, including advertising and special offers, can strengthen customers' positive perceptions of the brand and increase customer engagement. Competitive pricing that is balanced with product quality also plays an important role in influencing purchasing decisions and long-term loyalty. In conclusion, the right combination of the 4P elements can significantly increase customer loyalty, which is essential for business continuity and growth. This study provides insights for marketing practitioners in designing effective strategies to build and maintain customer loyalty.